Termo de Consentimento Livre e Esclarecido: significado para médicos e pacientes na assistência à saúde - Castro, Carolina Fernandes de (2021)
Bioethics has as one of its guiding principles the autonomy of human beings in their choices for their health. Based on this principle, informed consent emerged, also known as free and informed consent, where the health team has the duty to clarify any and all procedures proposed to the patient, as well as the diagnosis, prognosis, treatment, risks and the suggested treatment goals. As proof of the patient's self-determination, the Free and Informed Consent Form (ICF) was created, which must contain all the information previously mentioned, with the ICF being the main theme of this research project. Through a research on the topic with semi-structured interviews with eight doctors and nine patients in a hospital in the interior of Rio Grande do Sul, one can learn more about the topic. Although current and assiduous, the term still points out some difficulties experienced by the health team regarding its use, the objective, the language used and the way of presenting it. It was noticed through the interviews that the ICF is being used in a different way from its initial proposal, for patient protection it has also started to be used as a defense for health professionals, mainly doctors, in case of any technical error. This work investigated the meaning for doctors and patients in relation to the free and informed consent term, through semi-structured interviews in a hospital in the interior of Rio Grande do Sul, using Bardin's content analysis techniques (2010).